Point of Purchase Communication Promotion Media on Library Use by Library - Majidah, Majidah (Edulib, 2022)
In introducing library facilities, collections, and services, libraries often use promotional media known as Point of Purchase communications. However, the influence of each promotional media that uses library services has yet to be identified in detail by visitors. Thus this research was conducted to provide the answer. This study used an explanatory survey as a method with a questionnaire as an instrument. This survey collected 93 respondents as a sample from visitors to the Indonesian University of Education library registered as a population. The results showed that the Point of Purchase communication media utilized by the Indonesian University of Education library are leaflets, booklet, poster,X-banner, hanging mobile, table tent. And the promotional media for hanging mobile and shelf talkers greatly influenced visitors using library facilities. In addition, table tents and hanging mobile are media that influence visitors in using library collections and services. Meanwhile, booklets, posters, and shelf talkers do not make users use library services.